Method of manufacturing carbon paste-based electrode for optoelectronic device and optoelectronic device comprising carbon paste-based electrode
By using a conductive paste composed of carbon black, graphite and polymer binder, the problem of high drying temperature of the perovskite solar cell electrode layer is solved, and the manufacturing of a flexible and robust conductive layer is achieved, reducing costs and improving manufacturability.
Patent Information
- Application Number
- CN202411885980.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-24
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing perovskite solar cells have poor manufacturability, especially the drying temperature of the electrode layer may damage the perovskite layer, and the precious metal electrodes are costly and cannot be expanded in synthesis.
A conductive paste containing carbon black, graphite and a polymer binder with a softening point between 80°C and 150°C was used to form a flexible and compatible conductive layer with a perovskite layer by mixing and dissolving in a substituted benzene solvent.
The fabrication of flexible, robust conductive layers is achieved at a temperature without damaging the perovskite layer, reducing production costs and improving the manufacturability of perovskite solar cells.
Smart Images

Figure CN119894339A_ABST
Abstract
Description
Technical Field
[0001] The present technology relates to a method of making a strong conductive electrode that is compatible with perovskite layers. More specifically, it is a carbon slurry-based electrode that can be dried at low temperatures and is flexible. Background Art
[0002] Metal halide perovskite photovoltaic technology has experienced rapid development in the past few years, with laboratory efficiencies of 25% for small-area devices, which are competitive with silicon solar cells. At the same time, the pursuit of large-area perovskite solar cells has attracted increasing attention in recent years. For the manufacture of large-area perovskite films, industrial processes such as slot die coating, doctor blade coating, sheet-to-sheet and roll-to-roll manufacturing can be used. In such processes, several parameters usually need to be precisely adjusted and modulated to obtain films with sufficient quality for photovoltaic applications. The dynamic coating process in these methods may require precise tolerances on the machinery involved in the manufacturing. Such methods usually manufacture a single film during each round of coating.
[0003] Thin film devices are formed using several materials layered on top of each other by printing, coating with polymer inks or by vacuum deposition on substrates. The substrate in the thin film device may contain polyethylene terephthalate (PET), polyethylene naphthalate (PEN), fluorine-doped tin oxide (FTO) and indium tin oxide (ITO) as the initial layer.
[0004] The relatively poor manufacturability of perovskite solar cells when using existing processes is a significant barrier to wider adoption of these cells. For example, the drying of the electrode layer is at temperatures that can degrade the perovskite layer.
[0005] Carbon pastes have been developed to replace precious metals (e.g., gold) in optoelectronic devices (e.g., perovskite solar cells). In addition to being compatible with fast roll-to-roll and sheet-to-sheet processes, carbon electrodes are a good choice to replace expensive precious metal electrodes due to their good work function, high chemical stability, and carrier transport properties. However, metal-based electrodes are not chemically inert, are expensive, and their synthesis is not scalable.
[0006] What is needed is a method of making a conductive layer for use in optoelectronic devices, most notably perovskite photovoltaic devices. It would be preferred if the method was scalable, performed at temperatures that do not damage the perovskite layer, and inexpensive. It would be preferred if the conductive layer was flexible. Summary of the invention
[0007] The present technology is a method for making a conductive layer for use in optoelectronic devices, most notably perovskite photovoltaic devices. The method is scalable, is performed at temperatures that do not damage the perovskite layer, and is low-cost. The conductive layer is flexible.
[0008] In one embodiment, a method for manufacturing a perovskite photovoltaic stack is provided, the method comprising: selecting a stack comprising a perovskite layer, an electron transport layer, a bottom electrode and a glass substrate; mixing carbon black, graphite and a polymer binder having a softening point between 80°C and 150°C in a substituted benzene solvent, wherein the ratio of carbon black to graphite is between 1:1 and 3:7 w / w, and the total amount of carbon black and graphite (combined) to the polymer binder is between 2:1 and 4:1 w / w to provide a conductive paste; coating the perovskite layer with the conductive paste to provide a conductive coating; drying the conductive coating to provide a conductive layer; and applying an encapsulation layer to the conductive layer to manufacture the perovskite photovoltaic stack.
[0009] The method may further include selecting a polymer binder from the group consisting of thermoplastic polyurethanes, thermoplastic polyolefin elastomers, styrene block copolymers, ethylene-vinyl acetate copolymers, and hard-soft segment copolymers.
[0010] The method may further include selecting styrene-butadiene-styrene as the polymer binder.
[0011] The method may further include selecting chlorobenzene as the substituted benzene solvent.
[0012] In the method, the ratio of carbon black to graphite may be 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder may be between 3:1-4:1 w / w.
[0013] In another embodiment, a method for manufacturing a photovoltaic device is provided, the photovoltaic device comprising a perovskite layer, the method comprising: mixing carbon black and graphite in a solvent, the ratio of carbon black to graphite being 1:1 to 3:7 w / w, to provide a mixture; drying the mixture to provide carbon powder; selecting a polymer binder having a softening point between 80°C and 150°C; dissolving the polymer binder in a substituted benzene solvent; mixing the dissolved polymer binder with carbon powder, the ratio of polymer binder to carbon powder being 1:2 to 1:5 w / w, to provide a conductive paste; coating the perovskite layer with the conductive paste to provide a conductive coating; and drying the conductive coating at 60°C to 120°C to provide a conductive layer, thereby manufacturing a photovoltaic device comprising a perovskite layer.
[0014] The method may further include selecting a polymer binder from the group consisting of thermoplastic polyurethanes, thermoplastic polyolefin elastomers, styrene block copolymers, ethylene-vinyl acetate copolymers, and hard-soft segment copolymers.
[0015] The method may further include selecting styrene-butadiene-styrene as the polymer binder.
[0016] The method may further include selecting toluene as the substituted benzene solvent.
[0017] The method may further include adding a semiconductor material to the carbon powder.
[0018] The method may further include adding carbon nanowires or carbon nanotubes to the carbon powder.
[0019] In the method, the ratio of carbon powder to carbon nanowires or carbon nanotubes may be 10:1 w / w.
[0020] In the method, the ratio of carbon black to graphite may be 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder may be between 3:1-4:1 w / w.
[0021] In another embodiment, a conductive paste for coating a perovskite layer is provided, the conductive paste comprising carbon black, graphite and a polymer binder in a substituted benzene solvent, wherein the ratio of carbon black to graphite is between 1:1 and 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder is between 2:1 and 4:1 w / w, and wherein the polymer binder has a softening point between 80°C and 150°C.
[0022] In the conductive paste, the polymer binder may be styrene-butadiene-styrene.
[0023] In the conductive paste, the ratio of carbon black to graphite may be 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder may be between 3:1-4:1 w / w.
[0024] In the conductive paste, the substituted benzene solvent may be toluene.
[0025] In the conductive paste, the carbon black may be acetylene black.
[0026] The conductive paste may further include a semiconductor material.
[0027] The conductive paste may further include nanowires or nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a schematic diagram of the photovoltaic stack.
[0029] Figure 2 is a block diagram of a method of manufacturing a photovoltaic stack.
[0030] Figure 3 yes Figure 2 A block diagram of an alternative embodiment of the method.
[0031] Figure 4 yes Figure 2 A block diagram of another alternative embodiment of the method.
[0032] Figure 5 is a graph showing the effect of different ratios of carbon powder and polymer binder on resistivity. DETAILED DESCRIPTION
[0033] Unless expressly provided otherwise, the following rules of interpretation apply to this specification (written specification and claims): (a) all words used herein should be interpreted as the appropriate part of speech or number (singular or plural) as the case may be; (b) the singular terms "a", "an" and "the" used in this specification and the appended claims include plural references unless the context clearly indicates otherwise; (c) the preceding term "about" applied to a stated range or value indicates an approximate value within the range or value and the deviation of the measurement method known or expected in the art; (d) unless otherwise indicated, the words "herein", "herein" and "herein" shall refer to the range or value of the invention. (e) descriptive headings are used for convenience only and shall not control or affect the meaning or structure of any part of the specification; and (f) “or” and “any” are not exclusive, and “include” and “including” are not limiting. In addition, the terms “comprising”, “having”, “including” and “containing” are to be construed as open-ended terms (i.e., meaning “including but not limited to”) unless otherwise indicated.
[0034] Unless otherwise indicated herein, the numerical ranges listed herein are intended only as a shorthand method of referring individually to each individual value in the range, and each individual value is incorporated into the specification as if it were individually listed herein. When a specific numerical range is provided, it should be understood that, unless the context clearly dictates otherwise, each intermediate value between the upper and lower limits of the range (accurate to one tenth of the unit of the lower limit) and any other specified value or intermediate value in the stated range are included. All smaller sub-ranges are also included. The upper and lower limits of these smaller ranges are also included, except for any explicitly excluded limits in the stated range.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the relevant art. Although any methods and materials similar or equivalent to those described herein can also be used, only acceptable methods and materials are now described.
[0036] definition:
[0037] Carbon black: In the context of the present technology, carbon black is a quasi-crystalline carbon with a high surface area to volume ratio.
[0038] Acetylene black: In the context of the present technology, acetylene black is a specific form of carbon black and is produced by an acetylene thermal decomposition process. Detailed description of the invention:
[0040] Figure 1 1 , a photovoltaic stack is shown, generally depicted as 10 . It comprises an encapsulation layer 12 , a top electrode 14 or upper conductive layer, a perovskite layer 16 , an electron transport layer 18 , a bottom electrode 20 and a glass substrate 22 .
[0041] The upper conductive layer 14 is made of conductive paste. In one embodiment, the conductive paste is carbon paste. Carbon paste is a combination of carbon powder and polymer binder. The carbon powder is carbon black and graphite and optionally carbon nanowires or carbon nanotubes. The polymer binder is styrene-butadiene-styrene (SBS).
[0042] In another embodiment, the conductive paste is a carbon paste, which is a combination of carbon powder and a polymer binder. The carbon powder is a combination of acetylene black and graphite. The polymer binder is styrene-butadiene-styrene (SBS).
[0043] In another embodiment, the polymer binder is one or more from thermoplastic polyurethane (TPU), thermoplastic polyolefin elastomer (TPO), styrene block copolymer (SBC), ethylene-vinyl acetate copolymer (EVA), and hard-soft segment copolymer.
[0044] In another embodiment, the polymer binder is selected from polymer resins having a softening temperature of 80°C to 150°C.
[0045] In another embodiment, the polymer binder is selected from polymer resins having a melting point between 80°C and 150°C.
[0046] In another embodiment, the carbon slurry comprises a semiconductor material selected from the group consisting of CuInGaS2, Cu2ZnSnS4, chalcogenide semiconductors, CuInS2, CuPc, spiro-MeOTAD, oxide nanoparticles and carbon-based two-dimensional materials. These are added at a ratio of 1:10 w / w of semiconductor to carbon powder.
[0047] Figure 2 A method for manufacturing a photovoltaic stack is shown. Carbon black is mixed 100 with graphite in a solvent, which may be polar or non-polar, such as, but not limited to, water, alcohol, or an organic solvent (e.g., toluene), using, for example, but not limited to, ball milling, shear stress, and blending. Ball milling is performed at room temperature at 100 to 400 revolutions per minute (rpm), or at a higher rpm (e.g., but not limited to, 600 rpm) in the case of refrigeration or cooling with liquid nitrogen. The ratio of carbon black to graphite is about 1:1.5 w / w to 1:2 w / w to 3:7 w / w. The mixture is dried 102 to provide carbon powder. Optionally, the resulting carbon powder is sieved. A polymer binder is dissolved 104 in an organic solvent, such as, but not limited to, ethyl acetate or substituted benzene (e.g., but not limited to, toluene, chlorobenzene, or xylene). For SBS and toluene, the ratio of polymer binder to solvent is about 1:3 w / w. Carbon powder is mixed 106 with a dissolved polymer binder in a binder:carbon powder ratio of about 1:1 to about 1:6 w / w to provide a conductive paste. The conductive paste is then applied 108 to the perovskite layer 16 using, for example, but not limited to, doctor blade coating to provide a conductive coating. The conductive coating is dried 110 at between 70°C and 100°C for thirty minutes to provide a conductive layer 14 on the perovskite layer 16 of a nearly complete photovoltaic stack 10, after which only the encapsulation layer is added to provide a complete photovoltaic stack 10. Drying can also be performed at 60°C to 120°C for between 15 and 120 minutes. The encapsulation layer 12 is applied 112 to provide the photovoltaic stack 10.
[0048] In another embodiment, the ratio of carbon black to graphite is 1:1 w / w.
[0049] In one embodiment, toluene is used as a solvent both for mixing to provide the conductive powder and for dissolving the binder. The resulting conductive slurry is applied to the perovskite layer to provide a conductive coating, which is dried at room temperature for about 6 to about 12 hours. The ratio of carbon black and graphite to toluene is 1:5 w / w. The ratio of polymer binder to toluene is 1:3 w / w.
[0050] exist Figure 3 In the alternative embodiment shown, carbon black is mixed 200 with graphite in a solvent, which may be polar or non-polar, such as, but not limited to, water, alcohol, or an organic solvent (e.g., toluene), using, for example, but not limited to, ball milling, shear stress, and blending. The ratio of carbon black to graphite is about 1:1.5 w / w to 1:2 w / w to 3:7 w / w. Ball milling is performed at room temperature at 100 to 400 revolutions per minute (rpm), or at a higher rpm (e.g., but not limited to, 600 rpm) under refrigeration or cooling with liquid nitrogen. The mixture is dried 202. Carbon nanotubes or nanowires are added 204 to the carbon powder, with a ratio of carbon nanotubes or nanowires to the carbon powder of about 1:10 w / w. Semiconductor materials may also be added to the carbon powder at the same 1:10 ratio. The polymer binder is dissolved 206 in an organic solvent, such as, but not limited to, ethyl acetate or a substituted benzene (e.g., but not limited to, toluene, chlorobenzene, or xylene). For SBS and toluene, the ratio of polymer binder to solvent is about 1:3 w / w. The carbon powder is mixed 208 with a dissolved polymer binder in a ratio of about 1:1 to about 1:6 w / w to provide a conductive paste. The conductive paste is then applied 210 to the perovskite layer 16 using, for example, but not limited to, doctor blade coating. The resulting conductive coating is dried 212 at between 70° C. and 100° C. for thirty minutes to provide a conductive layer 14 on the perovskite layer 16 of a nearly complete photovoltaic stack 10, after which only the encapsulation layer is added to provide a complete photovoltaic stack 10. Drying can also be performed at 60° C. to 120° C. for between 15 and 120 minutes. The encapsulation layer 12 is applied 214 to provide the photovoltaic stack 10. In another embodiment, the ratio of carbon black to graphite is 1:1 w / w.
[0051] exist Figure 4 In the alternative embodiment shown, carbon black is mixed 300 with graphite and a polymer binder in an organic solvent, such as, but not limited to, ethyl acetate or substituted benzenes (such as, but not limited to, toluene, chlorobenzene, or xylene) using, for example, but not limited to, ball milling, shear stress, and blending. The ratio of carbon black to graphite is between 1:1.5 and 3:7 w / w, and the total amount of carbon black and graphite to the polymer binder is between 2:1 and 4:1 w / w. Ball milling is performed at room temperature at 100 to 400 revolutions per minute (rpm) or higher rpm. The resulting conductive slurry is then applied 302 to the perovskite layer 16 using, for example, but not limited to, blade coating to provide a conductive coating. The conductive coating is dried 304 at room temperature for about 6 to about 12 hours. An encapsulation layer 12 is applied 306 to provide a photovoltaic stack 10. In another embodiment, the ratio of carbon black to graphite is 1:1 w / w.
[0052] Regardless of the method used, the resulting conductive layer has the following characteristics: it is compatible with the perovskite layer, has high conductivity, is flexible (which is necessary for making flexible carbon-based perovskite solar cells), is strong (the perovskite layer coated with the conductive layer showed no signs of damage after being immersed in water for 5 minutes). The conductive layer is also strong and intact after being sonicated in an acidic aqueous solution at pH 2 for 10 minutes, and can be dried at temperatures between 70°C and 100°C (which is a temperature range compatible with all perovskite layers). The conductive layer provides an integrated, uniform, smooth and crack-free carbon-based electrode.
[0053] Example
[0054] like Figure 5 As shown, different ratios of carbon powder to polymer binder were investigated to determine which ratio provided low resistivity. It was found that ratios of carbon powder (carbon black and graphite) to polymer binder of 2:1, 3:1 and 4:1 w / w provided low resistivity.
[0055] As shown in Table 1, it was further found that carbon black to graphite ratios of 9:11, 2:3, and 3:7 w / w provided low resistivity. A ratio of 1:1 w / w provided higher resistivity but the highest efficiency. 3:7 w / w had the lowest resistivity but slightly lower efficiency than 1:1 w / w.
[0056] Table 1: Photovoltaic parameters of carbon-based perovskite solar cells with a carbon powder to polymer binder ratio of 3:1 w / w and different ratios of acetylene black (AB) to graphite (G).
[0057] Ratio of AB to G, w / w Resistivity efficiency 1:0 434 6.7 1:1 4.53 14.75 9:11 3.92 13.9 2:3 3.85 14.15 3:7 3.57 14.28 0:1 61.47 6.24
[0058] As shown in Table 2, at all ratios of carbon powder to polymer binder, the 1:4 ratio of acetylene black to graphite provided high resistivity. The lowest resistivity was obtained at a 3:7 w / w ratio of acetylene black to graphite and 3:1 and 4:1 w / w ratios of carbon powder to polymer binder. In terms of efficiency, the best efficiency was obtained at a 3:7 ratio of acetylene black to graphite and a 3:1 w / w ratio of carbon powder to polymer binder. The efficiency was lower at 2:1 and 5:1 w / w ratios of carbon powder to polymer binder.
[0059] Table 2: Photovoltaic properties of carbon-based perovskite solar cells with different ratios of carbon powder to polymer binder and different ratios of acetylene black to graphite.
[0060]
[0061] Water contact angles were also studied, with higher contact angles being preferred over lower contact angles. The ratios of carbon black to graphite were 1:0, 1:1, 9:11, 2:3, 7:13, 3:7, and 0:1 w / w. A ratio of 7 parts carbon black to 13 parts graphite w / w provided the highest angle. A ratio of 1:0 w / w provided the lowest water contact angle, followed by 2:3 w / w.
[0062] The effects of different non-polar solvents were investigated and toluene, xylene and chlorobenzene were found to be suitable solvents. As shown in Table 3, among the non-polar solvents, chlorobenzene provided the lowest resistivity, while toluene was the most efficient. Toluene also provided the largest water contact angle.
[0063] Table 3: Photovoltaic properties of carbon-based perovskite solar cells with different nonpolar solvents.
[0064] Solvents Resistivity efficiency Toluene 5.01 16.5 Xylene 5.11 13.97 chlorobenzene 3.46 14.71
[0065] The lowest resistivity was found when the ratio of acetylene black to graphite was 3:7 w / w as shown in Table 4. Similarly, the highest efficiency was found when the ratio of acetylene black to graphite was 3:7 w / w.
[0066] Table 4: Photovoltaic properties of carbon-based perovskite solar cells with a carbon powder to polymer binder ratio of 3:1 w / w and different ratios of acetylene black to graphite.
[0067] Ratio of AB to G, w / w Resistivity efficiency 1:4 11.31 14.38 6:19 7.86 14.67 27:73 4.94 15.56 3:7 3.78 15.96
[0068] Based on these results, it appears that a ratio of 3:1 or 4:1 w / w of carbon powder to polymer binder provides better results than 2:1 or 5:1 w / w. It appears that a ratio of 3:7 w / w of carbon black or acetylene black to graphite provides the lowest resistivity and generally the highest efficiency, with only a 1:1 w / w ratio having slightly higher efficiency but with higher resistivity. No single solvent outperformed the others, however xylene was inferior to toluene and chlorobenzene in both resistivity and efficiency.
[0069] Although exemplary embodiments have been described in conjunction with examples of what are currently considered to be the most practical and / or suitable embodiments possible, it should be understood that these descriptions are not limited to the disclosed embodiments, but rather are intended to cover various modifications and equivalent arrangements within the spirit and scope of the exemplary embodiments. Using only routine experimentation, those skilled in the art will recognize or be able to ascertain many equivalents to the specific exemplary embodiments specifically described herein. These equivalents are intended to be included within the scope of the appended claims or claims filed subsequently.
Claims
1. A method for manufacturing a perovskite photovoltaic stack, the method comprising: Selecting a stack comprising a perovskite layer, an electron transport layer, a bottom electrode and a glass substrate; mixing carbon black, graphite and a polymer binder having a softening point between 80°C and 150°C in a substituted benzene solvent, wherein the ratio of carbon black to graphite is between 1:1 and 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder is between 2:1 and 4:1 w / w to provide a conductive paste; coating the perovskite layer with the conductive paste to provide a conductive coating; drying the conductive coating to provide a conductive layer; and applying an encapsulation layer to the conductive layer, thereby producing a perovskite photovoltaic stack.
2. The method of claim 1, further comprising selecting the polymer binder from the group consisting of thermoplastic polyurethanes, thermoplastic polyolefin elastomers, styrene block copolymers, ethylene-vinyl acetate copolymers, and hard-soft segment copolymers.
3. The method of claim 1, further comprising selecting styrene-butadiene-styrene as the polymer binder.
4. The method of claim 3, further comprising selecting chlorobenzene as the substituted benzene solvent.
5. The method according to claim 4, wherein the ratio of carbon black to graphite is 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder is between 3:1-4:1 w / w.
6. A method of manufacturing an optoelectronic device, the optoelectronic device comprising a perovskite layer, the method comprising: Mixing carbon black and graphite in a solvent in a ratio of carbon black to graphite of 1:1 to 3:7 w / w to provide a mixture; drying the mixture to provide carbon powder; selecting a polymer binder having a softening point between 80° C. and 150° C.; dissolving the polymer binder in a substituted benzene solvent; mixing the dissolved polymer binder with the carbon powder in a ratio of polymer binder to carbon powder of 1:2 to 1:5 w / w to provide a conductive paste; coating the perovskite layer with the conductive paste to provide a conductive coating; and drying the conductive coating at 60° C. to 120° C. to provide a conductive layer, thereby manufacturing a photovoltaic device including the perovskite layer.
7. The method of claim 6, further comprising selecting the polymer binder from the group consisting of thermoplastic polyurethanes, thermoplastic polyolefin elastomers, styrene block copolymers, ethylene-vinyl acetate copolymers, and hard-soft segment copolymers.
8. The method of claim 6, further comprising selecting styrene-butadiene-styrene as the polymer binder.
9. The method of claim 8, further comprising selecting toluene as the substituted benzene solvent.
10. The method of claim 9, further comprising adding a semiconductor material to the carbon powder. 11 . The method according to claim 10 , further comprising adding carbon nanowires or carbon nanotubes to the carbon powder.
12. The method according to claim 11, wherein the ratio of carbon powder to carbon nanowires or carbon nanotubes is 10:1 w / w.
13. The method of claim 12, wherein the ratio of carbon black to graphite is 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder is between 3:1-4:1 w / w.
14. A conductive paste for coating a perovskite layer, the conductive paste comprising carbon black, graphite and a polymer binder in a substituted benzene solvent, wherein the ratio of carbon black to graphite is between 1:1 and 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder is between 2:1 and 4:1 w / w, and wherein the polymer binder has a softening point between 80°C and 150°C.
15. The conductive paste of claim 14, wherein the polymer binder is styrene-butadiene-styrene.
16. The conductive paste according to claim 15, wherein the ratio of carbon black to graphite is 3:7 w / w, and the ratio of the total amount of carbon black and graphite to the polymer binder is between 3:1-4:1 w / w. The conductive paste according to claim 16 , wherein the substituted benzene solvent is toluene. The conductive paste according to claim 17 , wherein the carbon black is acetylene black. The conductive paste according to claim 18 , further comprising a semiconductor material.
20. The conductive paste according to claim 19, further comprising nanowires or nanotubes.